Gerontological Issues and Challenges of the Retirees: Implications for Ameliorating Strategies - C.U, Ugwu; O.C., Ene; E. K., Nwala (Journal of Home Economics Research, 2024)
Living a healthy life and maintaining functional health after retirement is an ideal plan of all workers in different sectors. Ageing as an aspect of gerontology, is characterized by multiple challenges that affect functional health and wellness in later life. This paper presented the categories of ageing, issues relating to gerontology in ageing population, and the challenges of the retirees. It also discusses various efforts by individuals as well as groups in ameliorating these challenges. The implications for ameliorating strategies are also discussed. It is recommended, among others, that pre-retirement programmes should be organized in different sectors in order to expose and prepare employees on the issues and anticipated challenges to be faced after retirement.